The Impact of Negative Reinforcement on Fifth Grade Students' Science Learning Process - Sandy Yulianti; M. Jaya Adi Putra; Zariul Antosa (Program Studi Pendidikan Guru Sekolah Dasar, FKIP, Universitas Riau, 2019)
This study attempts to investigate the positive and the negative impact of negative reinforcement on fifth-grade students’ science learning process. This study was carried out in elementary school 177 Pekanbaru. The kind of research is a qualitative study, and data were collected using video recording, observation, the questionnaire, and interview. Ten learning and teaching activities were conducted in two classrooms, 5 times in VA and 5 times in VB. The results show that the positive impact of negative reinforcement is to increased students’ motivation to study science. While the negative impact of negative reinforcement is, to have students’ ton fear or vexation dislike to their teacher. The students feel discomfort because the teacher often punished students whenever they made mistakes